Edukasi Tanaman Herbal Untuk Pengontrol Tekanan Darah - Amelia Dini Anggraini Silalahi; Joni Siagian; Khairunnisa Batubara; Naila Khalis; M. Hafinawa Husaini; Salsa Billa (Jurnal Pengabdian Keperawatan Dan Kesehatan Holistik, 2026)
Hypertension is an increase in blood pressure that causes persistent symptoms in target organs, such as: Stroke, coronary heart disease in blood vessels and heart muscle. It is estimated that cases of hypertension will increase by 80% by 2025, especially in developing countries, from 639 million cases in 2000 to 1.15 billion cases in 2025. Treatment of hypertension is generally done with medical drugs, but the use of medicinal plants as complementary therapy is increasingly in demand. The goal of this Community Service Program is to educate and empower the community to actively participate in managing their health, particularly in controlling blood pressure by utilizing existing natural resources and reducing dependence on chemical medications. This activity was conducted through outreach, discussions, and pre- and post-tests on 35 community members. This community service activity was held on Thursday, November 13, 2025 at the homes of residents of Dusun II, Desa Sei Kamah II, Kecamatan Sei Dadap, Kabupaten Asahan. The implementation of PkM activities showed that there was an increase in the knowledge of PkM participants about herbal plants for controlling blood pressure in the Sei Kamah II Village community, where before the education, community knowledge was in the poor category, namely 27 people (77.1%), and the good category was 8 people (22.7%). After the education, there was an increase in the knowledge of PkM participants, namely the good category of 33 people (94.3%) and the poor category of 2 people (5.7%).